2001
DOI: 10.1038/sj.onc.1204233
|View full text |Cite
|
Sign up to set email alerts
|

PTOV1, a novel protein overexpressed in prostate cancer containing a new class of protein homology blocks

Abstract: In a search for molecular markers of progression in prostate cancer by means of di erential display, we have identi®ed a new gene, which we have designated PTOV1. Semiquantitative RT ± PCR has established that nine out of 11 tumors overexpress PTOV1 at levels signi®cantly higher than benign prostatic hyperplasia or normal prostate tissue. The human PTOV1 protein consists almost entirely of two repeated blocks of homology of 151 and 147 amino acids, joined by a short linker peptide, and is encoded by a 12-exon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
122
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(128 citation statements)
references
References 37 publications
(26 reference statements)
5
122
0
1
Order By: Relevance
“…6). However, there are two domains with a fold that resembles that of Med25 ACID in another human protein, PTOV1, which is overexpressed in prostate cancers 48 and is involved in cell proliferation 49 ( Supplementary Fig. 4).…”
Section: Discussionmentioning
confidence: 99%
“…6). However, there are two domains with a fold that resembles that of Med25 ACID in another human protein, PTOV1, which is overexpressed in prostate cancers 48 and is involved in cell proliferation 49 ( Supplementary Fig. 4).…”
Section: Discussionmentioning
confidence: 99%
“…ARC92 exhibits homologs in higher eukaryotes, including frog, zebrafish, fruit f ly, and plants; however, we have been unable to identify homologs in Caenorhabditis elegans or yeast, suggesting that ARC92 may either have diverged during evolution or that it has emerged as a subunit in higher eukaryotes in response to the demands imposed by an increasingly complex gene regulatory apparatus (data not shown). A homology search also revealed that a segment of ARC92 appears to be highly related to a repeated sequence in a protein of unknown function that was identified based on its overexpression in prostate tumors (PTOV1) (26) (Fig. 1B).…”
Section: Identification Of Arc92 As a Specific Target Of The Vp16 Actmentioning
confidence: 99%
“…Transient transfection of chimeric green fluorescent protein-PTOVI forces the entry of cells into the S phase ofthe cell cycle, as shown by double fluorescent imaging for green fluorescent protein and for Ki67, and also by flow cytometry. These observations suggest that PTOVI contribute to the proliferative status of cells (1,4,5).…”
Section: Discussionmentioning
confidence: 73%
“…It has been suggested that overexpression of PTOVI can contribute to the proliferative status of prostate tumour cells and thus to their biological behaviour (1)(2)(3)(4)(5). The protein PTOVI is overexpressed immunohistochemically in over 70% of PCa cases (3,5).…”
mentioning
confidence: 99%